Michael Dukakis Rally at Fresno Amtrak Station - Watkins, Howard::::::::: (1988)
Assemblymember Bruce Bronzan, Michael Dukakis, and Lt. Governor Leo McCarthy holding hands and arms up in victory to cheering crowd Dukakis turned and talking with Bronzan